Personnel policy of preserving intellectual capital: awaiting Industry 5.0 - N.V. Zachosova; V.M. Kimlyk; A.V. Zamohylna (Економіка, управління та адміністрування)
The purpose of the study was to substantiate and develop the theoretical and methodological provisions of the personnel policy of enterprises, which will be adapted to the realities of wartime and suitable for use in the conditions of the spread of the trend of Industry 5.0. Urgent issues of formation and implementation of personnel policy tools of business entities in modern economic conditions have been determined. It is substantiated that Industry 5.0 dictates the parameters of human-centricity in business, i.e., the basis of personnel policy should be a motivational mechanism, a toolkit for the development of the employee's potential, his acquisition of new professional characteristics under the influence of a constant and continuous learning process, the inclination to which is stimulated by the company's management. The importance of personnel policy for preserving the intellectual potential of the enterprise and forming its personnel capital is analyzed. The essence and main goals of personnel policy in the conditions of war and in anticipation of Industry 5.0 were studied. It has been established that the effectiveness of personnel management can be increased by improving the mechanism of forming the personnel policy of the enterprise and directing it to preserve and increase the intellectual potential of the business entity. The elements of the personnel policy implementation mechanism at the domestic enterprise are outlined. Factors influencing the personnel policy of domestic enterprises in wartime and peacetime conditions are specified.